2022
DOI: 10.1080/21655979.2022.2073114
|View full text |Cite
|
Sign up to set email alerts
|

Circular_0086414 induces SPARC like 1 (SPARCL1) production to inhibit esophageal cancer cell proliferation, invasion and glycolysis and induce cell apoptosis by sponging miR-1290

Abstract: Circular RNA (circRNA) plays an important role in cancer progression. Here, we investigated the function of circ_0086414 in the malignant progression of esophageal cancer (EC). RNA expression of circ_0086414, microRNA-1290 (miR-1290), and SPARC like 1 ( SPARCL1 ) was detected by quantitative real-time polymerase chain reaction. The protein levels of N-cadherin, E-cadherin, and SPARCL1 were checked by Western blotting analysis. Cell proliferation was investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, some circRNAs have been shown to increase apoptosis of ESCC cells (93,94). Jiang et al (95) found that low circ0086414 expression correlates with poor prognosis in patients with ESCC. They observed that circ0086414 inhibits tumor cell proliferation, suppresses glycolysis and increases apoptosis in ESCC cells.…”
Section: Ncrnas Regulate Proliferation and Apoptosis Of Escc Cellsmentioning
confidence: 99%
“…Moreover, some circRNAs have been shown to increase apoptosis of ESCC cells (93,94). Jiang et al (95) found that low circ0086414 expression correlates with poor prognosis in patients with ESCC. They observed that circ0086414 inhibits tumor cell proliferation, suppresses glycolysis and increases apoptosis in ESCC cells.…”
Section: Ncrnas Regulate Proliferation and Apoptosis Of Escc Cellsmentioning
confidence: 99%
“…Lentivirus-mediated overexpression of circFAM120B also decreased CRC tumor growth in the xenograft tumor model [ 108 ]. Furthermore, the specific lentivirus-mediated enforced expression of circRPN2, circ_0004913, and circ_0001445 in HCC [ 59 , 109 , 110 ] and circular_0086414 in EC [ 111 ] restrained tumorigenesis in vitro.…”
Section: Clinical Significance Of Glycolysis-associated Circrnas In G...mentioning
confidence: 99%
“…Many circRNAs affect glycolysis by modulating transcription factors [ 48 , 49 ]. Hypoxia inducible factor-1α (HIF-1α) is a nuclear transcription factor produced by cancer cells adapting to hypoxia environments.…”
Section: Circrna and Cancer Cell Metabolic Reprogrammingmentioning
confidence: 99%